1991
DOI: 10.3109/08916939109006751
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cytotoxic Cells by Syngeneic Prostate Antigens in Experimental Autoimmune Vesiculo-Prostatitis

Abstract: In our experimental model of autoimmune vesiculo-prostatitis, obtained by immunization with syngeneic male accessory glands (MAG) and complete Freund's adjuvant, the presence of specific autoreactive cells with cytotoxic activity against prostate antigens was studied. The specific cytotoxicity generated in MAG immunized rats was tested using 51Cr labelled syngeneic prostate cells or labelled chicken erythrocytes coated with specific antigens (MAG homogenate or chromatographic fractions from prostate homogenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…As in Wistar rats, MAG elicits both a humoral and a cell-mediated response in NOD mice. In the rat model, we have shown that the cell-mediated response gave rise to reactive oxygen intermediates and to CD8 + cytotoxic T cells, two agents potentially capable of causing tissue damage [12,13]. A future objective is to identify which of these effector agents are responsible for the destructive lesions seen in NOD mice and whether B cells and antibodies detected soon after immunization also participate in the pathogenic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Wistar rats, MAG elicits both a humoral and a cell-mediated response in NOD mice. In the rat model, we have shown that the cell-mediated response gave rise to reactive oxygen intermediates and to CD8 + cytotoxic T cells, two agents potentially capable of causing tissue damage [12,13]. A future objective is to identify which of these effector agents are responsible for the destructive lesions seen in NOD mice and whether B cells and antibodies detected soon after immunization also participate in the pathogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…EAP can be adoptively transferred into na茂ve Wistar rats by whole spleen cells of autoimmune donors, but not by spleen cells which have been depleted of T lymphocytes prior to transfer in vitro [11]. Pathogenic reactive oxygen intermediates released by macrophages [12] and cytotoxic T lymphocytes [13] have been demonstrated in diseased rats and may be responsible for tissue alterations observed on histological sections.…”
Section: Introductionmentioning
confidence: 99%
“…88 It has been speculated that inflammatory damage induced in this model might be the result of generation of autoreactive cytotoxic cells, increased levels of radical oxidative species from prostatic infiltrating macrophages, and upregulated mast cell degranulation. [89][90][91] These studies do not identify the specific prostatic proteins that are the targets on an immune response. The immunogenicity of prostatic acid phosphatase (PAP) as a target for the induction of an immune response in 6-to 8-week-old Copenhagen rat was investigated by Fong et al 92 They demonstrated that immunization with recombinant rat or human PAP leads to a significant antibody response, 4 weeks after the final boost, but does not generate cytotoxic T lymphocytes (CTL) or result in autoimmune prostatitis.…”
Section: Immune-induced Prostatitis Modelsmentioning
confidence: 99%
“…Both cytotoxic T lymphocytes and pathogenic reactive oxygen intermediates released by macrophages have been identified in diseased rats and are probably responsible for the tissue alterations observed on histological sections (6,7).…”
Section: Introductionmentioning
confidence: 99%